Correlation Between Sarcopenia and Oral Health in Patients on Chronic Hemodialysis - Petra Kovačević Totić; Iva Klarić Puđa; Karla Kovačević Čorak; Velimir Altabas; Milan Milošević; Selma Cvijetić Avdagić; Karmela Altabas (Life)
Patients on hemodialysis have signs of chronic systemic inflammation and a higher incidence of sarcopenia. Poor oral health can also trigger systemic inflammation and thus affect sarcopenia. The study included 100 patients on chronic hemodialysis who underwent oral status, routine laboratory measurements, bioimpedance analysis, hand grip strength measurement, and two questionnaires regarding oral health and sarcopenia. Data were analyzed using the Fisher exact test and the Mann–Whitney U test. In total, 28.0% of the participants had sarcopenia. The median total number of erupted teeth in all patients was 12.0 (7.0–23.0). A positive correlation of the total number of erupted teeth and erupted premolars with sarcopenia was confirmed (p = 0.035). CRP was significantly elevated in patients with sarcopenia (p = 0.035). Laboratory parameters showed that the blood albumin level was reduced in all patients (p = 0.002). The median overall score of the SarQoL questionnaire for all participants was 60.37 (43.87–70.61), which indicates that patients on hemodialysis are aware of their limitations caused by sarcopenia. Moreover, SarQoL was significantly negatively correlated with sarcopenia. This study confirmed poorer oral health in hemodialysis patients who had sarcopenia. Therefore, intervention studies are needed to improve the oral health of patients on HD, which could possibly influence the incidence of sarcopenia.